Chronic respiratory disorders due to aberrant innominate artery: a case series and critical review of the literature - Adele Corcione; Melissa Borrelli; Leonardo Radice; Oliviero Sacco; Michele Torre; Francesco Santoro; Gaetano Palma; Eleonora Acampora; Francesca Cillo; Pietro Salvati; Angelo Florio; Francesca Santamaria (BMC, 2023)
Abstract Background Tracheal compression (TC) due to vascular anomalies is an uncommon, but potentially serious cause of chronic respiratory disease in childhood. Vascular slings are congenital malformations resulting from abnormal development of the great vessels; in this group of disorders the most prevalent entity is the aberrant innominate artery (AIA). Here we provide a report on diagnosis and treatment of AIA in nine children with unexplained chronic respiratory symptoms. We describe the cases, perform a literature review, and provide a discussion on the diagnostic workup and treatment that can help manage AIA. Methods Clinical history, diagnostic procedures and treatment before and after the AIA diagnosis were retrospectively reviewed in nine children (5 boys and 4 girls), who were referred for recurrent-to-chronic respiratory manifestations over 10 years (2012-2022). We performed a comprehensive report on the ongoing clinical course and treatment as well as an electronic literature search on the topic. Results Diagnoses at referral, before AIA was identified, were chronic dry barking cough associated with recurrent pneumonia (n = 8, 89%), lobar/segmental atelectasis (n = 3, 33%), atopic/non atopic asthma (n = 3, 33%); pneumomediastinum with subcutaneous emphysema complicated the clinical course in one case. When referred to our Unit, all patients had been previously treated with repeated antibiotic courses (n = 9, 100%), alone (n = 6, 67%) or combined with prolonged antiasthma medications (n = 3, 33%) and/or daily chest physiotherapy (n = 2, 22%), but reported only partial clinical benefit. Median ages at symptom onset and at AIA diagnosis were 1.5 [0.08-13] and 6 [4-14] years, respectively, with a relevant delay in the definitive diagnosis (4.5 years). Tracheal stenosis at computed tomography (CT) was ≥ 51% in 4/9 cases and ≤ 50% in the remaining 5 subjects. Airway endoscopy was performed in 4 cases with CT evidence of tracheal stenosis ≥ 51% and confirmed CT findings. In these 4 cases, the decision of surgery was made based on endoscopy and CT findings combined with persistence of clinical symptoms despite medical treatment. The remaining 5 children were managed conservatively. Conclusions TC caused by AIA may be responsible for unexplained chronic respiratory disease in childhood. Early diagnosis of AIA can decrease the use of expensive investigations or unsuccessful treatments, reduce disease morbidity, and accelerate the path toward a proper treatment.